Earthquake Cycle Deformation Associated With the 2021 MW 7.4 Maduo (Eastern Tibet) Earthquake: An Intrablock Rupture Event on a Slow‐Slipping Fault From Sentinel‐1 InSAR and Teleseismic Data. Issue 11 (15th November 2022) - Fang, Jin; Ou, Qi; Wright, Tim J.; Okuwaki, Ryo; Amey, Ruth M. J.; Craig, Tim J.; Elliott, John R.; Hooper, Andy; Lazecký, Milan; Maghsoudi, Yasser
Abstract: In the continents, the importance of earthquakes that occur away from major block‐bounding faults is still debated. The 21 May 2021 M W  ∼ 7.4 Maduo earthquake occurred on a secondary fault away from previously‐identified major block boundaries. Here we use 7 years of Sentinel‐1 Interferometric Synthetic Aperture Radar (InSAR) time series (between October 2014 and November 2021) to determine the distribution of coseismic slip and early postseismic afterslip following the Maduo earthquake, and the preceding interseismic strain accumulation. We devised a 13‐segment 3‐D fault geometry constrained by the SAR range offsets and the distribution of relocated aftershocks and used a Bayesian method incorporating von Karman regularization to solve for coseismic slip and afterslip models. We also used teleseismic waveforms as a standalone inversion to show the rupture evolution in space and time during the earthquake, finding that it propagates bilaterally with three notable rupture episodes. Our preferred coseismic self‐similar slip model shows a moderate shallow slip deficit, with the majority of moment release occurring in the depth interval of 1–10 km. The coseismic slip deficit is taken up in part by afterslip at shallow (<4 km) depths that grows linearly with time during the first ∼6 months, and at >10 km depths where afterslip grows logarithmically with time. We suggest that this heterogeneity is likely controlled by spatial variations in fault friction related to lithology. We discuss the implications for seismic hazard away from major tectonic block boundaries in light of our observations of the earthquake cycle on this intrablock fault. Plain Language Summary: Collision between the Indian and Eurasian plates has created the largest deforming region on the planet. Part of the resultant deformation is accommodated by movements on block‐bounding faults where major earthquakes usually occur. A large earthquake ruptured a slow‐moving fault away from the major pre‐identified block boundaries on 21 May 2021. We used 7 years of satellite radar images to measure the deformation that occurred before, during, and after the earthquake. We also used seismic observations to investigate the temporal evolution of the earthquake rupture. Our model agrees with the results from field mapping. Postseismic deformation at shallow and deep depths shows different temporally varying behavior, which is likely caused by the frictional properties of the fault associated with different physical characteristics of rocks. The causative fault was accumulating relatively subtle strain before the earthquake. We observed the strain being localized on one of the faults in the block interior, highlighting elevated earthquake potential in the future. Key Points: We present the earthquake cycle deformation for the 2021 Maduo earthquake from Sentinel‐1 Interferometric Synthetic Aperture Radar and teleseismic waveforms Coseismic slip deficit is taken up by shallow and deep afterslip with different temporal behavior; this may be controlled by lithology Interseismic strain observed in the interior of a mapped tectonic block highlights importance of seismic hazard away from block boundaries